KEY DETERMINANTS OF GREEN PERFORMANCE MANAGEMENT PRACTICES IN MULTINATIONAL COMPANY IN INDONESIA - Ferinia, Rolyana (Ekonomica Sharia: Jurnal Pemikiran dan Pengembangan Ekonomi Syariah, 2025)
This study analyzes the interconnections between essential elements of Green Human Resource Management (GHRM), including Green Employee Separation (GES), Green Performance Management (GPM), Green Employee Engagement (GEE), and Green rraining and Development (GTD), in multinational corporations in Indonesia. Data were gathered from 81 employees using a Likert-scale questionnaire and processed by Structural Equation Modeling–Partial Least Squares (SEM-PLS) for hypothesis testing, moderation analysis, and variance explanation. The results demonstrate that GEE and GTD have substantial beneficial impacts on GPM, however GES does not show a moderating effect. GPM is recognized as the primary factor influencing organizational green performance, with GEE, GTD, and GES together representing 69.3% of its variance. This research introduces an integrated paradigm that identifies employee engagement, training and development, and retention as essential drivers for enhancing organizational success in green performance management.